2004
DOI: 10.1038/sj.bmt.1704664
|View full text |Cite
|
Sign up to set email alerts
|

Reduced-intensity conditioning using TBI (8 Gy), fludarabine, cyclophosphamide and ATG in elderly CML patients provides excellent results especially when performed in the early course of the disease

Abstract: Summary:Allogeneic bone marrow or stem cell transplantation is a curative therapeutic option for chronic myelogenous leukemia. In order to decrease the toxicity of the procedure, the dosage of total body irradiation was reduced from 12 to 8 Gy and subsequently the dose of cyclophosphamide from 120 to 80 mg/kg. The purine analogue fludarabine, ATG, cyclosporine A and a short course of methotrexate were given for immune suppression. So far, 35 elderly CML patients with sibling and unrelated donors have been tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Such "nonmyeloablative" or "reduced intensity conditioning" transplantations should be particularly valuable for patients older than 50 years or younger patients with comorbid conditions. Although a number of small singlecenter series and an analysis of outcome for 186 patients treated in 38 centers reporting to the EBMT have been published, [18][19][20][21][22] it is not yet possible to conclude that a reduced intensity conditioning allo-SCT offers a major advantage for the younger patient who would otherwise be a candidate for an allograft with conventional conditioning. It is undoubtedly an option for the older patient who could not normally be considered for a transplantation with myeloablative conditioning.…”
Section: Imatinibmentioning
confidence: 99%
“…Such "nonmyeloablative" or "reduced intensity conditioning" transplantations should be particularly valuable for patients older than 50 years or younger patients with comorbid conditions. Although a number of small singlecenter series and an analysis of outcome for 186 patients treated in 38 centers reporting to the EBMT have been published, [18][19][20][21][22] it is not yet possible to conclude that a reduced intensity conditioning allo-SCT offers a major advantage for the younger patient who would otherwise be a candidate for an allograft with conventional conditioning. It is undoubtedly an option for the older patient who could not normally be considered for a transplantation with myeloablative conditioning.…”
Section: Imatinibmentioning
confidence: 99%
“…44 Reduced intensity conditioning (RIC) is currently being evaluated for CML. [45][46][47][48] The EBMT has reported on registry data of 187 patients (median age, 50 years) who were submitted to RICalloHSCT between 1994 and 2002, mainly from matched-related donors. 49 Three-year OS was 70% for the patients with an EBMT score of 0 to 2, 50% for the patients with a score of 3 to 4, and about 30% for those with a score of 5 or higher.…”
Section: Not Includedmentioning
confidence: 99%
“…Our data and that from others indicate that RIST is effective for allografting individuals with CML; [6][7][20][21][22][23][24][25] despite the fact that most studies with reduced-intensity conditioning have a relatively short follow-up, there is information indicating that the procedure has a lower prevalence and severity of GVHD, 26 and similar efficacy to conventional allografting; the low prevalence of chronic GVHD in this study supports this observation, which may be related to the diminished organ damage induced by the conditioning schedule. Since this method is more feasible and affordable for patients and physicians in developing countries, the number of allografts in these places has increased substantially, as well as the publications related to bone marrow transplantation stemming from places where this therapeutic maneuver was considered as unaffordable previous to the development of this technology.…”
Section: Discussionmentioning
confidence: 84%
“…6 Later, Or et al, 7 they found a 5-year overall survival (OS) of 85%. 7 More recently, Weisser et al, 20 in Germany reported their experience in 35 elderly CML given RIST in different phases of the disease, emphasizing the benefit of early transplantation, within the first year of diagnosis. Other authors have included CML patients in their reports of RIST.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation